The Estimation of Oil Palm Carbon Stock in Sembilang Dangku Landscape, South Sumatra - Rachdian, Azar; ., Hariyadi; Setiawan, Yudi (Media Konservasi, 2018)
Oil palm has the ability to sequester carbon dioxide stored as carbon stock. This study aimed to estimate carbon stock  in some age classes, to determine the relationship between Normalized Difference Vegetation Index (NDVI) and carbon stock, and to estimate the distribution of oil palm carbon stock in Landscape Sembilang Dangku. Estimation of carbon stock  were carried out at the non productive age plant phase namely <2 years, 2-3 years, and the productive plant age  phase namely 4-10 years and> 10 years. The carbon stock estimation used allometric equations. Landsat 8 Operational Land Imager (OLI) /Thermal Infrared Sensor (TIRS)  was analyzed to determine NDVI.  Making a map of the classification of carbon stock distribution using Software QGIS Las Palmas 2.18.0. The results showed that the carbon stock in the age class <2 years was 9.50 ton C/ ha, the age class of 2-3 was 9.62 ton C/ha, the age of 4-10 was 28.23 ton C/ha and in the age class> 10 was 79.83 ton C/ha. The relation between NDVI with carbon stock had a strong correlation (r = 0.9972) with regression equation Y = 638.13x - 242.65.  Carbon stock distribution  was  based on percentage of area as follows: <15 ton C/ha covering an area of 26.52%, 15-25 ton C/ha covering an area of 5.29%, 26-70 ton C ha covering an area of 35.41%, and > 70 ton C/ha 32.78%. Keywords: age class, carbon stock, landscape, NDVI